Prospective study of patients with membranous patch over the tonsil at GIMS, Kalaburagi - Melkundi, Renuka S.; Patil, Siddaram (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Current study was done to know various clinical aspects of membranous patch over the tonsil. Methods: Data for the study were collected from patients who presented with membranous patch over the tonsil in the department of ENT at GIMS, Kalaburagi from January 2019 to December 2019. This is a prospective case study. 225 patients were included in the study. Once patient was presented to us detailed history, examination and necessary investigations were done. Results: The present study included 225 patients out of which out of which females were 132 (59%) and males were 93 (41%). The predominant clinical features were sore throat (225 cases), fever (212 cases), dysphagia (90 cases) and bull neck (45 cases). The most common cause of membranous patch over tonsil was found to be diphtheria (68%) followed by streptococcal tonsillitis (30%) and others (2%). In our study microbiological investigations like Albert stain was positive in 153 cases and culture was positive in 140 cases. Conclusions: It was observed in our study that diphtheria constitutes the majority (68%) and the incidence of adult is almost on par with paediatric age group. Despite of UIP we have seen increased incidence in the adult age group. Hence it requires the health agencies and the Government to increase immunization coverage, as India has witnessed the highest number of cases in the world for the year 2015. As evident from the shift in age groups being infected, adult booster dose has to be introduced at 10 years interval.